A study of SeqA subcellular localization in Escherichia coli using photo-activated localization microscopy. (9th October 2015) - Mika, Jacek T.; Vanhecke, Aster; Dedecker, Peter; Swings, Toon; Vangindertael, Jeroen; Van den Bergh, Bram; Michiels, Jan; Hofkens, Johan
Abstract : Escherichia coli ( E. coli ) cells replicate their genome once per cell cycle to pass on genetic information to the daughter cells. The SeqA protein binds the origin of replication, oriC, after DNA replication initiation and sequesters it from new initiations in order to prevent overinitiation. Conventional fluorescence microscopy studies of SeqA localization in bacterial cells have shown that the protein is localized to discrete foci. In this study we have used photo-activated localization microscopy (PALM) to determine the localization of SeqA molecules, tagged with fluorescent proteins, with a localization precision of 20–30 nm with the aim to visualize the SeqA subcellular structures in more detail than previously possible. SeqA–PAmCherry was imaged in wild type E. coli, expressed from plasmid or genetically engineered into the bacterial genome, replacing the native seqA gene. Unsynchronized cells as well as cells with a synchronized cell cycle were imaged at various time points, in order to investigate the evolution of SeqA localization during the cell cycle. We found that SeqA indeed localized into discrete foci but these were not the only subcellular localizations of the protein. A significant amount of SeqA–PAmCherry molecules was localized outside the foci and in a fraction of cells we saw patterns indicating localization at the membrane. Using quantitative PALM, we counted protein copy numbers per cell, protein copy numbers per focus, the numbers of foci per cell and the sizes of the SeqA clusters. The data showed broad cell-to-cell variation and we did not observe a correlation between SeqA–PAmCherry protein numbers and the cell cycle under the experimental conditions of this study. The numbers of SeqA–PAmCherry molecules per focus as well as the foci sizes also showed broad distributions indicating that the foci are likely not characterized by a fixed number of molecules. We also imaged an E. coli strain devoid of the dam methylase ( Δdam ) and observed that SeqA–PAmCherry no longer formed foci, and was dispersed throughout the cell and localized to the plasma membrane more readily. We discuss our results in the context of the limitations of the technique.